2010
DOI: 10.1021/nn102345f
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Delivery of Bioactive Molecules using Light-Addressable Nanocapsules

Abstract: This paper describes a method by which molecules that are impermeable to cells are encapsulated in dye-sensitized lipid nanocapsules for delivery into cells via endocytosis. Once inside the cells, the molecules are released from the lipid nanocapsules into the cytoplasm with a single nanosecond pulse from a laser in the far red (645nm). We demonstrate this method with the intracellular release of the second messenger IP 3 in CHO-M1 cells, and report that calcium responses from the cells changed from a sustaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 41 publications
1
34
0
Order By: Relevance
“…The binding event then causes calcium (Ca 2+ ) release from the endoplasmic reticulum into the cytosol . Cells were incubated with plasmonic liposomes containing 730 × 10 −6 m IP 3 . Both MDA‐MB‐231 cancer cells and primary culture of dorsal root ganglia (DRG) neurons were tested.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding event then causes calcium (Ca 2+ ) release from the endoplasmic reticulum into the cytosol . Cells were incubated with plasmonic liposomes containing 730 × 10 −6 m IP 3 . Both MDA‐MB‐231 cancer cells and primary culture of dorsal root ganglia (DRG) neurons were tested.…”
Section: Resultsmentioning
confidence: 99%
“…Upon near‐infrared light illumination, photosensitizer molecules produce singlet oxygen to oxidize vehicle structure and thus uncage the packaged biomolecules, or the payload. Among different vehicles, photosensitizer‐modified liposome is one of the most widely used vehicles for photochemically triggered uncaging . For instance, Kohane and co‐workers synthesized a new photosensitizer that when incorporated into liposomes, enabled light‐triggered lipid oxidation and tetrodotoxin uncaging to block the sciatic nerve .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the attachment of a HIV-TAT peptide to a potent JNK1 inhibitor by Stebbins and coworkers, allowed the authors to achieve JNK1 inhibition both in cultured cells and in glucose-intolerant mice (Stebbins et al 2011). Furthermore, we have shown that it is possible to photothermally release bivalent inhibitors that are encapsulated in dye-sensitized lipid nanocapsules (Gregersen et al 2010). Examples of this type point to the likelihood of increased use of bisubstrate and bivalent inhibitors in cellular studies.…”
Section: Discussionmentioning
confidence: 99%
“…Like the bisubstrate inhibitors described above, the first cellular experiments with SNAP-tag-based bivalent inhibitors involved the use of an intra-cellular delivery method (Gregersen et al 2010). Specifically, a fully assembled bivalent inhibitor of Abl was encapsulated in dye-sensitized lipid nanocapsules, which were taken up by BCR-Abl-dependent Ba/F3 cells through endocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…79 By selectively labeling SNAPtag fusion proteins, which display a specificity ligand from their N- or C-termini, with an ATP-competitive inhibitor, potent and selective bivalent inhibitors of several kinases have been generated. 1013 Our previously described SNAPtag-based bivalent inhibitors relied on the use of genetically-encoded peptide ligands that had previously been characterized to be selective for a targeted site of interest in biochemical screens (referred to here as consensus-binding motifs ) as secondary specificity ligands. While this strategy led to impressive selectivity amongst closely related kinases, consensus-binding motifs often possess modest affinity and selectivity for their respective targets.…”
Section: Introductionmentioning
confidence: 99%